Prevalence of Vector‐Borne Pathogens in Southern California Dogs With Clinical and Laboratory Abnormalities Consistent With Immune‐Mediated Disease. (30th May 2017) - Kidd, L.; Qurollo, B.; Lappin, M.; Richter, K.; Hart, J.R.; Hill, S.; Osmond, C.; Breitschwerdt, E.B.
Abstract : Background: Studies investigating the prevalence of vector‐borne pathogens in southern California dogs are limited. Occult infections might be misdiagnosed as idiopathic immune‐mediated disease. Hypothesis/Objectives: (1) To determine the prevalence of vector‐borne pathogens in southern California dogs with compatible clinical findings using PCR and serologic panels and (2) to determine whether testing convalescent samples and repeating PCR on acute samples using the same and different gene targets enhance detection. Animals: Forty‐two client‐owned dogs with clinical signs of vector‐borne disease presenting to specialty practices in San Diego County. Methods: Combined prospective and retrospective observational study. Forty‐two acute and 27 convalescent samples were collected. Acute samples were prospectively tested for antibodies to Rickettsia, Ehrlichia, Bartonella, Babesia, Borrelia, and Anaplasma species . PCR targeting Ehrlichia, Babesia, Anaplasma, hemotropic Mycoplasma, and Bartonella species was also performed. Retrospectively, convalescent samples were tested for the same organisms using serology, and for Ehrlichia, Babesia, Anaplasma, and Bartonella species using PCR. Acute samples were retested using PCR targeting Ehrlichia and Babesia species. Results: Evidence of exposure to or infection with a vector‐borne pathogen was detected in 33% (14/42) of dogs. Ehrlichia and Babesia species were most common; each was identified in 5 dogs. Convalescent serologic testing, repeating PCR, and using novel PCR gene targets increased detection by 30%. Conclusions and Clinical Importance: Repeated testing using serology and PCR enhances detection of infection by vector‐borne pathogens in dogs with clinical signs of immune‐mediated disease. Larger prevalence studies of emerging vector‐borne pathogens in southern California dogs are warranted.